Effects of penguin guano and moisture on nitrogen biological fixation in maritime Antarctic soils - Perez, Cecilia A.; Aravena Donaire, Juan Carlos; Ivanovich, Cristobal; McCulloch, Robert (My University, 2017)
Biological nitrogen fixation (BNF) is a high energy-demanding process that may be inhibited by penguin guano. We tested this hypothesis in Ardley Island by measuring BNF in biological soil crusts (BSC) directly within a Penguin Colony and in sites unaffected by penguins. We also explored the effect of adding guano to BSCs in sites free of the influence of penguins. Water availability is also one of the most limiting elements for life in the Antarctica, and we expected that a wetter growing season would stimulate BNF. To evaluate the effect of moisture on BNF, we added water to BSCs under laboratory conditions and estimated BNF by means of the acetylene reduction assay during three growing seasons (2012, 2013 and 2014), with contrasting temperature and precipitation conditions. The results reveal an almost complete inhibition of N fixation in the BSCs of the Penguin Colony. In sites free of ammonium and phosphate in rainwater, BNF rates reached up to 3 kg N ha(-1) year(-1) during warmer and wetter years. The addition of guano to BSCs significantly inhibited the rates of BNF. In laboratory incubations, the addition of water significantly stimulated rates of BNF during the warmer growing season with more sunshine hours. The likely increases in soil moisture levels due to climate change and glacier melting in the Antarctic Peninsula may enhance the rates of BNF. However, this may be constrained by accompanying changes in the distribution of Penguin Colonies.
Keywords: biological nitrogen fixation; ardley island; penguin colony; palaeobeaches